Perancangan Antena Mikrostrip Array 2 Elemen untuk Aplikasi 5G Menggunakan Software CST - Mutiara Widasari Sitopu; Suherman Suherman; Febrin Aulia Batubara; Nur Adilah; Ummu Handasah; Muhammad Sukri Habibi Daulay; Charla Tri Selda Manik; Samuel Gerardo Simanjuntak (LKP Unity Academy, 2025)
The development of 5G communication technology requires antenna devices that have good performance, small size, and are able to operate at high frequencies. One alternative is a microstrip array antenna because it has advantages in size, ease of manufacture, and the ability to increase gain. This study discusses the design process and performance testing of a microstrip array antenna that functions at a frequency of 5GHz for use in 5G communication systems. The design and testing process were carried out using CST Studio Suite software. The simulation results show that the designed antenna is able to operate at a frequency of 5GHz with a return loss value of less than -10 dB, where the results obtained based on the simulation are -24.42dB. VSWR below 2, where the results obtained based on the simulation are 1.12, and desired bandwidth is wide, which is produced in this design is 380MHz. Thus, the designed two element microstrip array antenna has been successfully designed with the standard parameters specified for use in a 5G network communication system.